HUBUNGAN ANTARA MOTIVASI DENGAN PRESTASI AKADEMIK MAHASISWA STIA LAN BANDUNG - Ely Sufianti1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
The phenomenon shows that some government apparatus up grade their education level for the sake of certificate not for self development. It raises the question of what really motivates them. Those all drive this study. The study aims at finding out the relationship between motivation and academic performance of the students of the National Agency for State Administration - School of Administration (STIA LAN) Bandung. The result shows that the students (who are all government apparatus), both assigned and consented, hold higher intrinsic motivation than extrinsic motivation. However, it proves no significant difference on their academic performance. The research result also demonstrates significant and positive relationship between motivation and academic performance.